(untitled) (Annals of Medical Research, 2024)
Aim: Previous studies have indicated that definitive chemoradiotherapy and upfront surgery have comparable survival rates, and definitive chemoradiotherapy is a more applicable treatment option in resectable locally advanced esophageal squamous cell cancer (ESCC). We compared definitive chemoradiotherapy to upfront surgery for survival in locally advanced ESCC patients who denied the standard treatment approach, receiving definitive chemoradiotherapy or upfront surgery. Materials and Methods: One hundred eighty eight locoregional ESCC patients with thoracic and distal involvement who had upfront surgery were compared with those who received chemoradiotherapy but declined surgery, although their tumor was resectable at presentation. Patients who underwent upfront surgery with negative surgical margins were included. The upfront surgery group received no adjuvant treatment (chemotherapy or radiotherapy). The definitive chemoradiotherapy group received standard therapy with 50.4 Gray/28 fractions/6 weeks concomitantly with weekly Paclitaxel 50 mg/m2 and Carboplatin AUC 2 combination regimen. Results: A total of 102 patients (54.3%) underwent surgery up front, whereas 86 patients (45.7%) had definitive chemoradiotherapy. The median follow-up of the study was 31 months. Definitive chemoradiotherapy had a median disease-free survival (DFS) of 39 months compared to 16 months for upfront surgery (p:0.005). Median overall survival (OS) was 29 months in upfront surgery and 47 months in definitive chemoradiotherapy (p=0.01). Although the multivariate Cox regression analysis found no difference in DFS between upfront surgery and definitive chemoradiotherapy groups, OS was greater with the latter (HR, 0.69; 95% CI, 0.47 to 1.00; p=0.05). Conclusion: In this non-randomized retrospective analysis, definitive chemoradiotherapy improved overall survival compared to upfront surgery in locally advanced ESCC patients.